5w-3=4w

Simple and best practice solution for 5w-3=4w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5w-3=4w equation:


Simplifying
5w + -3 = 4w

Reorder the terms:
-3 + 5w = 4w

Solving
-3 + 5w = 4w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-4w' to each side of the equation.
-3 + 5w + -4w = 4w + -4w

Combine like terms: 5w + -4w = 1w
-3 + 1w = 4w + -4w

Combine like terms: 4w + -4w = 0
-3 + 1w = 0

Add '3' to each side of the equation.
-3 + 3 + 1w = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 1w = 0 + 3
1w = 0 + 3

Combine like terms: 0 + 3 = 3
1w = 3

Divide each side by '1'.
w = 3

Simplifying
w = 3

See similar equations:

| -9k+5=-10k-4 | | -9k+5=-10j-4 | | -2s-6=-s | | -34=8x-5(1-7x) | | 4j=5j-7 | | 4x+8=12x-12 | | 3g=-7+4g | | 9(t-5)+6t=5(3t+4)-10 | | m=-0.4n+28 | | y+y-y-y+y-1=18 | | -93-4v=-10v+3 | | 2x^4-9x^2-16x=0 | | 3h+3h-6h+2j-2=12 | | 2x^4-9x^2-16=0 | | 18j+2j-10j-5j-4j=16 | | 18j+2j-10-5j-4j=16 | | 13p-6p-5p=18 | | 9t+(3f)t+13= | | 27-×/4=x/5 | | 4+7x-3=9x+13-6x | | 6j+-2j+14j-7j+-9n-(-19)=-15 | | m(a+5)=Kfora | | -0.1x^2-x+31=0.1x^2+2x+11 | | 6j+-2j+14j-7j+-9-(-19)=-15 | | 0.2x^2+x-20=0 | | 6j+-2j+14j-7j+(-19)=-15 | | 6j+2j+14j-7j+(-19)=-15 | | r-r+5r-2r=9 | | -5c+14c+-7=11 | | 5b-19b-(-20b)-(-14)=-10 | | 32+0.90m=2(31+0.30m) | | 20m-10m+2m-8m+2m=6 |

Equations solver categories